2017
DOI: 10.3389/fmicb.2017.02229
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Monitoring Strategies to Detect Precipitation-Induced Microbial Contamination Events in Karstic Springs Used for Drinking Water

Abstract: Monitoring of microbial drinking water quality is a key component for ensuring safety and understanding risk, but conventional monitoring strategies are typically based on low sampling frequencies (e.g., quarterly or monthly). This is of concern because many drinking water sources, such as karstic springs are often subject to changes in bacterial concentrations on much shorter time scales (e.g., hours to days), for example after precipitation events. Microbial contamination events are crucial from a risk asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 40 publications
1
21
0
Order By: Relevance
“…Especially the hyporheic zone between surface water and groundwater provides living space for a variety of microorganisms and biological activity within this zone contributes to the natural attenuation of contaminants from surface water infiltrating into the aquifer, usually resulting in minor changes in the biogeochemical processes of the reservoirs ( Boulton et al, 1998 ; Hiscock and Grischek, 2002 ). Although persistence of allochthonous microorganisms in the groundwater bodies is unlikely ( Pronk et al, 2009 ), river bank filtration systems are considered to be vulnerable to extreme weather conditions such as floods and droughts ( Sprenger et al, 2011 ; Besmer et al, 2017 ). Increased water level differences between river and wells due to season and rain events as well as increased pumping rates at well sites shorten interstitial residence time of water and reduce bank filtration processes, resulting in increased entry of allochthonous microorganisms in the groundwater body ( Sprenger et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Especially the hyporheic zone between surface water and groundwater provides living space for a variety of microorganisms and biological activity within this zone contributes to the natural attenuation of contaminants from surface water infiltrating into the aquifer, usually resulting in minor changes in the biogeochemical processes of the reservoirs ( Boulton et al, 1998 ; Hiscock and Grischek, 2002 ). Although persistence of allochthonous microorganisms in the groundwater bodies is unlikely ( Pronk et al, 2009 ), river bank filtration systems are considered to be vulnerable to extreme weather conditions such as floods and droughts ( Sprenger et al, 2011 ; Besmer et al, 2017 ). Increased water level differences between river and wells due to season and rain events as well as increased pumping rates at well sites shorten interstitial residence time of water and reduce bank filtration processes, resulting in increased entry of allochthonous microorganisms in the groundwater body ( Sprenger et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…As alternative to toluidine blue staining, root sections were stained with SYBR green nucleic acid stain to highlight the bacteroidal zone based on staining of highly concentrated bacterial DNA. Nodules showed densely colonized central zones ( Figure 4 ), typical for dalbergioid nodules, in which the central tissue is uniformly infected ( Lavin et al, 2001 ), and infection by crack entry through lateral root junctions is common ( Coba de la Pena et al, 2017 ). Also, Pterocarpus is within the dalbergoid clade as part of the Pterocarpus clade ( Lavin et al, 2001 ).…”
Section: Resultsmentioning
confidence: 99%
“…The total microbial load has been retained a key driver of microbial alterations due to varying environmental factors and water treatment settings in numerous applications on either natural or engineered aquatic systems (Osman et al, 2008; Harry et al, 2016; Besmer et al, 2017). In this study, all selected early-warning monitoring techniques showed pioneering potential applicability to space and human-confined environments, given the necessity to overcome some basic drawbacks of cultivation-based approaches (i.e., time-to-result up to several days from sampling; growth of opportunistic microorganisms from stored analytical wastes).…”
Section: Discussionmentioning
confidence: 99%